DORA opens the door to a better agricultural information service - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Since 1991 CTA has been implementing a programme to supply agricultural reference books to documentation centres within agricultural educational institutions in ACP countries. Technical and educational reference publications are supplied in...